"Synthesis and study of novel biological active chalconyl-ester based bent-core LCs: Effect of tail/lateral group". (13th June 2018) - Desai, Vipul; Sharma, Vinay S.; Patel, R.B.
Abstract: A newly designed homologues series: 4-bromo-2-(3-(4-dimethyl amino) phenyl) acryloyl)-6-nitrophenyl-3-(4-n-alkoxy phenyl) acrylate has been synthesized and studied through chalconyl vinyl ester linking group at (ortho) position. Novel series consisted thirteen compounds, in which C1 to C5 homologue are nonliquid crystal, while C6 to C18 exhibits SmC and nematic phase at enantiotropically manner. Thus, present novel series is predominantly nematogenic and partly smectogenic mesophase. Mesophase image of present compounds are schlieren like, broken fan and threaded type textures measured by POM equipped with heating stage. All this compounds were characterized by FT-IR and 1 H NMR analysis. The mesomorphism is measured by POM, DSC and molecular packing is confirmed by XRD technique. Chalconyl ester based compounds C4 to C12 shows antibacterial as well as antifungal activity compared with corresponding standard drugs. Analytical and spectral data confirmed the molecular structures of the present V-shaped bent core homologous series. Graphical Abstract: